Exogenous application of salicylic acid to control coffee rust (Acta Scientiarum. Biological Sciences, 2021)
The exogenous application of salicylic acid can induce plant resistance against pathogens. However, little is known about the potential uses of this bioregulator for controlling coffee diseases. In this study, we assessed the effect of applying salicylic acid (SA – 150 mg L-1) on the management of coffee rust (Hemileia vastatrix) in a 7-year-old coffee plantation with low crop load (651.6 kg ha-1 in 2017). For comparison, plants were sprayed with protectant fungicide (copper hydroxide – CH) and standard fungicides (SF) used by local farmers (boscalid, pyraclostrobin + epoxiconazole, and copper hydroxide). Non-treated plants were included as a negative control. Five monthly applications were performed from November 2016 to March 2017. Rust incidence and severity, defoliation, and growth of plagiotropic branches were evaluated monthly. The activity of catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD) and total proteins was assessed one day after the first, third, and fifth product applications. Compared to untreated plants, SA reduced the severity and incidence of rust from 36.3 to 54.7%, while CH and SF reduced disease from 31.8 to 54.6% and from 83.8 to 88%, respectively. SA reduced defoliation by 54.1%. SA increased the concentration of CAT, APX, and SOD after the first application. However, this effect was not observed after subsequent applications. Foliar application of SA reduces the severity and incidence of coffee rust and defoliation in plants with a low crop load.